2017
DOI: 10.1002/jmv.24969
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of human metapneumovirus circulating during 2010‐2012 in children from Panama

Abstract: Human metapneumovirus (HMPV) is a common causative agent of severe respiratory tract infections in children under 5 years old, the elderly and immunocompromised patients, being responsible for 5-15% of all viral respiratory infections requiring hospitalization. Though HMPV was included in the surveillance program for respiratory viruses in 2010, its genotype distribution remains unknown. Herein, 45 positive samples to HMPV from children ≤5 years old were characterized by phylogenetic analysis based on N gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…In our study, the majority (71.8%; 221/308) of HMPV-positive patients were children between 0 to 5 years old, with more than the half of them under 1 year age (55.7%, 123/221). Consistent with our findings, several studies have reported this sensitivity of children under 5, especially in the first year life, to HMPV infection [2224]. This highest prevalence in children is believed to be due to a naive immune system for most of HMPV genotypes in early childhood.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the majority (71.8%; 221/308) of HMPV-positive patients were children between 0 to 5 years old, with more than the half of them under 1 year age (55.7%, 123/221). Consistent with our findings, several studies have reported this sensitivity of children under 5, especially in the first year life, to HMPV infection [2224]. This highest prevalence in children is believed to be due to a naive immune system for most of HMPV genotypes in early childhood.…”
Section: Discussionsupporting
confidence: 92%
“…A similar genotypic composition has been observed in several other studies [13, 32, 33]. And as in other studies conducted in Saudi Arabia [26], in Croatia [34], in Panama [24] or in Kenya [32], we have no strain belonging to genotype A1, supporting the idea that old lineages have been replaced by emerging genetic strains. Indeed, the A2c subgroup was present in Senegal throughout the study period, except in 2014 where it was not detected probably due to a non-exhaustive sequencing.…”
Section: Discussionsupporting
confidence: 90%
“…We identified the hMPV A 2 subtype and our results showed that it circulated in Córdoba during 2011. We did not detect subtypes A1, B1 and B2; a reason for this may have been we were not able to get high-quality RNA and/or optimal sequences from the years 2012 and 2013, however, other authors demonstrated that these subtypes are seldom reported [40]. In our country, Galiano (2006) demonstrated the circulation of A 1 , A 2 and B 2 subtypes; Velez Rueda (2013) showed that A 2 and B 2 subtypes co-circulated during 2009-2010, while hMPV A 2 was detected in 2011 [16,28].…”
Section: Discussionmentioning
confidence: 69%
“…Panama included HMPV surveillance in 2010 as part of the National Epidemiologic Surveillance System. A previous study [27] described a HMPV frequency among ≤5-year-olds hospitalized patients with ARI of 1.3% in 2011 and 13.9% in 2012, which may suggest important fluctuations over time. We did not detect HMPV in hospitalized children with ARI in 2016.…”
Section: Discussionmentioning
confidence: 87%